Changes in gastric cancer mortality in Peru before, during, and after the pandemic: a national interrupted time series analysisn - Benites-Goñi, Harold (2025)
Introduction: The diagnosis and treatment of gastric cancer may have been affected during the COVID-19 pandemic, ultimately influencing mortality from this disease. Objective: To evaluate changes in gastric cancer mortality during the COVID-19 pandemic years. Materials and methods: An interrupted time series analysis was conducted to assess changes in gastric cancer mortality. Data were obtained from the National Death Information System. Three periods were compared: pre-pandemic (2017–2019), pandemic (2020–2021), and post-pandemic (2022–2023). Segmented regression models were used. Results: Before the pandemic, an average of 2,107 deaths per year was recorded. During 2020 and 2021, mortality increased by 39% and 118%, respectively. The highest peaks occurred between April and July 2020. An additional rise was observed during the early months of 2021. Although mortality progressively declined in 2023, pre-pandemic levels were not restored. The analysis showed that observed deaths consistently exceeded expected projections through late 2022. Conclusions: The COVID-19 pandemic generated a temporary but significant increase in gastric cancer–related mortality in Peru.